Peripheral nerve stimulation in intractable neuropathic pain - Kozak, Jiri; Kobesova, Alena; Vrba, Ivan; Steindler, Jiri; Kolar, Pavel (Neuro endocrinology letters, 2011)
Peripheral nerve stimulation (PNS) is a neurostimulation analgesic technique. PNS is utilized to treat peripheral neuropathic pain. It is highly sophisticated and a specialized technique used where other forms of treatment have failed. This paper describes the PNS procedure, its therapeutic principles, indications, and the comprehensive care for patients after the PNS implant. First, we summarize our experience using this type of invasive treatment. In the second part, a case of intractable neuropathic pain following repeated surgery to the ulnar nerve is reported. Prior to PNS, the patient underwent multiple types of antineuralgic treatment with no significant result. Only after the PNS application, was a significant analgesic effect achieved.
Keywords: dospělí; Capsaicin; neuralgie; Electric Stimulation Therapy; Female; neurochirurgie; Electrodes, Implanted; Neurosurgery; Adult; ženské pohlaví; aplikace kožní; lidé; Neurologic Examination; Peripheral Nerves; Administration, Cutaneous; neurologické vyšetření; elektrostimulační terapie; Ulnar Neuropathies; periferní nervy; kapsaicin; implantované elektrody; neuropatie nervus ulnaris; Neuralgia; Ulnar Nerve; nervus ulnaris; Humans